Impact of long-term debt maturity and corporate social responsibility on default probability in developing countries - Badayi, Suleiman Ahmed; Tunde, Matemilola Bolaji; Amin Noordin, Bany Ariffin; Law, Wei Theng (Mattingley Publishing, 2020)
This paper examines the impact of long-term debt maturity and corporate social responsibility on probability of default in 17 developing countries during 2010-2017. We find evidence that long-term debt maturity increases probability of default. Moreover, we establish that firms that invest more in corporate social responsibility activities decrease their probability of default. Similar results are obtained after excluding Africa and Middle Eastern regions from the full sample. Additional robustness analysis suggests that macroeconomic variables impact negatively on the probability of default. The findings suggest that policymakers should design policies that encourages firms to increase their investments towards CSR activities in order to establish good reputation with various stakeholders, and hence decrease probability of default.